Penyuluhan Pertanian Berbasis Pupuk Organik untuk Meningkatkan Kemandirian Petani di Desa Payaman, Solokuro, Lamongan - Ahmad Zakariya Al Anshori; Ihsan Sholikin; Nur Habibi (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The potential of fertilizer resources must be studied and developed for the welfare of farmers. Gayam Hamlet, Payaman Village, Solokuro District, Lamongan Regency has the potential for livestock waste in the form of cow dung which can be used as a material for making fermented organic fertilizer. The objectives of this community service activity are: 1. Increase farmers' knowledge about the benefits of compounds and microbes contained in livestock manure. 2. Improve farmers' skills in techniques for making organic fertilizer from livestock manure. 3. Reduce confusion among communities who are dependent on subsidized fertilizers from the government which has been limited by Permentan No. 10 of 2022. The extension method consists of lectures, discussions, and demonstrations of making organic fertilizer from livestock manure. The extension activity was carried out at the residence of the Head of the Gapoktan Payaman Village, Solokuro District, Lamongan Regency in August 2023. The results of the activity evaluation showed an increase in participants' understanding and skills in making organic fertilizer, as evident from active participation in discussions, successful practical demonstrations, and participant feedback. Because no formal pre-test and post-test were conducted, this increase was reported qualitatively.